Analysis on vibration and shock response of a hybrid isolation system using dynamic vibration absorber with negative stiffness - Su Zhiwei (Zhongguo Jianchuan Yanjiu, 2019)
[Objectives] To meet the demand of on-board machinery for components with high transmission loss and vibration and shock isolation,[Methods] a hybrid vibration isolation system using Dynamic Vibration Absorber(DVA)with Negative Stiffness(NS)is proposed. Then the non-dimensional dynamic model of the proposed isolation system with rigid base is established,and the fixed-point method is employed to obtain the optimal parameters of stiffness ratio and damping ratio under the influence of exciting force. Runge-Kutta method is adopted to study the shock response of the proposed isolation system with optimal parameters by using different shock pulse widths under base excitation,and then this shock response is compared with that of the traditional DVA.[Results] It shows that the proposed isolation system has a transmission characteristic without a resonance peak by using certain parameters. The shock acceleration response and the relative displacement of the proposed isolation system are smaller than those of the traditional DVA by using different pulse widths.[Conclusions] The proposed isolation system provides a new approach for the design of the vibration absorber with high load carrying capacity and high transmission loss.